2022
DOI: 10.3390/ijms23073847
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis and MAPK Pathways

Abstract: Cancer is a leading cause of death worldwide. In many cases, the treatment of the disease is limited due to the metastasis of cells to distant locations of the body through the blood and lymphatic drainage. Most of the anticancer therapeutic options focus mainly on the inhibition of tumor cell growth or the induction of cell death, and do not consider the molecular basis of metastasis. The aim of this work is to provide a comprehensive review focusing on cancer metastasis and the mitogen-activated protein kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 243 publications
(301 reference statements)
0
27
0
Order By: Relevance
“…Similarly, the RELA proto-oncogene encodes a transcriptionally active subunit of the NF-kB complex that is strongly associated with PNST, but not FS or PWT DEGs ( Fig 5 ) and is being investigated as a therapeutic target [ 91 ]. The Ras-related protein gene RAP1A was also one of the most significantly expressed genes specific to PWTs ( Table 1 ) and Rap1A promotes cell migration and metastasis [ 92 , 93 ]. Inhibitors of factors mediating its activation have been examined for use as anti-cancer agents [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the RELA proto-oncogene encodes a transcriptionally active subunit of the NF-kB complex that is strongly associated with PNST, but not FS or PWT DEGs ( Fig 5 ) and is being investigated as a therapeutic target [ 91 ]. The Ras-related protein gene RAP1A was also one of the most significantly expressed genes specific to PWTs ( Table 1 ) and Rap1A promotes cell migration and metastasis [ 92 , 93 ]. Inhibitors of factors mediating its activation have been examined for use as anti-cancer agents [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent studies focused on the effects of the MAPK pathway on tumor development [ 7 , 10 , 13 , 17 ]. Recently published research work showed that the MAPK pathway not only regulates the behavior of tumor cells, but also the behavior of surrounding normal stromal cells in the TME (tumor microenvironment) during cancer pathogenesis [ 7 ]. The specific activities of the MAPK pathway components in tumor initiation and progression vary based on the stimuli and stromal cells involved in tumor growth [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published research work showed that the MAPK pathway not only regulates the behavior of tumor cells, but also the behavior of surrounding normal stromal cells in the TME (tumor microenvironment) during cancer pathogenesis [ 7 ]. The specific activities of the MAPK pathway components in tumor initiation and progression vary based on the stimuli and stromal cells involved in tumor growth [ 7 ]. Furthermore, the research about the effect of hypoxia on cancer cells showed that hypoxia-inducible transcription factor α (HIF1α) affects as a transcription factor many genes involved in anaerobic metabolisms, angiogenesis, and metastasis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations